Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Is it trivial to say $$\mathop {\lim }\limits_{n \to \infty } {(1 + {k \over n})^n} = e^{k},$$

considering the fact that we know $$\mathop {\lim }\limits_{n \to \infty } {(1 + {1 \over n})^n} = e?$$

share|cite|improve this question
The first limit is $e^k$. – user63181 Nov 15 '13 at 15:30
can you tell me why? – captain dragon Nov 15 '13 at 15:33
$\lim\limits_{n \to \infty } {\left(1 + \frac{k}{n}\right)^n} = \lim\limits_{n \to \infty } {(( 1 + \frac{1}{\frac{n}{k}})^{\frac{n}{k}}})^k=e^k$ – user35603 Nov 15 '13 at 15:36
oh, got it. please write it as an answer – captain dragon Nov 15 '13 at 15:37
please, fix the OP $e\to e^k$ – Ilya Nov 15 '13 at 15:49
up vote 8 down vote accepted

Since $\frac kn = \frac 1 {\frac nk}$ and $n = \frac nk \cdot k$ we have $$\lim_{n\to \infty} (1+\frac kn)^n = \lim_{n\to\infty} \left( (1 + \frac{1}{\frac nk})^{\frac nk} \right)^k = \left ( \lim_{u\to\infty} (1+\frac 1u)^u \right)^k = e^k$$ If $k<0$, you have $$(1+\frac 1u)^{-u} = \left((1+\frac 1u)^u\right)^{-1} \to e^{-1} \qquad (u\to\infty)$$

share|cite|improve this answer
That's fine for $k > 0$. But the statement is actually true for all $k$. – Robert Israel Nov 15 '13 at 15:42
@RobertIsrael Your assertion is correct, thanks.# – AlexR Nov 15 '13 at 15:45

Well, by (one) definition of $e$, we have $$e=\lim_{t\to\infty}\left(1+\frac1t\right)^t.$$ Now, in particular, if $k>0$, then letting $t=\frac nk,$ we find that $t\to\infty$ precisely as $n\to\infty,$ so that $$\begin{align}\lim_{n\to\infty}\left(1+\frac kn\right)^n &= \lim_{n\to\infty}\left(1+\frac kn\right)^{\frac nk\cdot k}\\ &= \lim_{t\to\infty}\left(1+\frac1t\right)^{tk}\\ &= \lim_{t\to\infty}\left(\left(1+\frac1t\right)^t\right)^k\\ &= \left(\lim_{t\to\infty}\left(1+\frac1t\right)^t\right)^k\\ &= e^k\end{align}$$ The $k=0$ case is trivial. To deal with the $k<0$ case, observe that $$1+\frac kn=\frac{n+k}{n}=\left(\frac{n}{n+k}\right)^{-1}=\left(1+\frac{-k}{n+k}\right)^{-1},$$ so letting $t=\frac{n+k}{-k},$ we once again have $t\to\infty$ as $n\to\infty,$ and so $$\begin{align}\lim_{n\to\infty}\left(1+\frac kn\right)^n &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-n}\\ &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-(n+k)+k}\\ &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-(n+k)}\left(1+\frac{-k}{n+k}\right)^k\\ &= \lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^{-(n+k)}\lim_{n\to\infty}\left(1+\frac{-k}{n+k}\right)^k\\ &= \lim_{n\to\infty}\left(1+\frac kn\right)^{\frac{n+k}{-k}\cdot k}\\ &= \lim_{t\to\infty}\left(1+\frac1t\right)^{tk}\\ &= \lim_{t\to\infty}\left(\left(1+\frac1t\right)^t\right)^k\\ &= \left(\lim_{t\to\infty}\left(1+\frac1t\right)^t\right)^k\\ &= e^k\end{align}$$

share|cite|improve this answer

By $\displaystyle\lim_{n\to\infty}\left(1+\frac{1}{n}\right)^n = e,n\in\mathbb{N}$, we have $$\lim_{x\to\infty}\left(1+\frac{1}{x}\right)^x = e,\quad x\in \mathbb{R}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.